‘No Diplomatic Negotiations or Insistence before the Ottoman Porte to Have Any Favorable Result...’: The Caucasus in Russian-Turkish Relations, Late Nineteenth and Early Twentieth Centuries - Karine R. Ambartsumyan; Mikayel A. Malkhasyan; Vahram R. Balayan (Oriental Studies, 2024)
Introduction. Being a key point on the Russian-Turkish agenda during the period in question, the Caucasus was influenced not only by the traditional logic of geopolitical rivalry between the two powers but also by somewhat tectonic shifts in the system of international relations. The world was anticipating a global war, and this did affect regional policies of the powers too. Moreover, the Caucasus was (and still is) particularly sensitive to geopolitical issues in general. So, the late nineteenth and early twentieth centuries witnessed an evolution in the foreign policy dimension across the Caucasus, since the more or less obvious confrontation was then replaced by complicated interactions between the powers, the latter never to exclude rivalry but would involve elements of constructive relationship as well. Materials and methods. The study is essentially interdisciplinary, which makes it possible to organically combine methods of historical research and some approaches to the study of international relations. The key sources are documents from the Archive of Foreign Policy of the Russian Empire, Archive of Russian State Military History, and State Archive of the Russian Federation. Results. One of the aspects of Russian-Turkish interaction was the migration of Muslims from both the North Caucasus and Transcaucasia: for a number of indigenous peoples religious commonness was reinforced by their Turkic roots. Historical sources confirm Turkey’s emissaries would launch active campaigns among local populations, while a group of Caucasians were actually residing in the two empires. So, the Caucasian borderland became a haven for ethnic Armenians seeking salvation from systematic violence in the Ottoman Empire. The compact Armenian-inhabited areas on both sides of the Russia-Turkey border made the problem of reforming Turkey’s Armenian wilayahs particularly urgent for Russian officials in St Petersburg and especially in the Caucasus. Conclusions. The work resumes on the eve of the war the Caucasus — despite being part of the Russian state — became a Russia-Turkey contact zone, which still implied hidden geopolitical rivalry.